2009
DOI: 10.1002/gps.2276
|View full text |Cite
|
Sign up to set email alerts
|

When the solution is part of the problem: problem solving in elderly suicide attempters

Abstract: SUMMARYObjectives-Depression, loss, and physical illness are associated with suicide in the elderly. However, the nature of individual vulnerability remains poorly understood. Poor problem solving has been suggested as a risk factor for suicide in younger adults. Unresolved problems may create an accumulation of stressors. Thus, those with perceived deficits in problem-solving ability may be predisposed to suicidal behavior. To test this hypothesis, we investigated whether elderly suicide attempters perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 43 publications
(56 reference statements)
3
56
3
2
Order By: Relevance
“…Deficits in problem solving abilities are particularly pronounced in older adults with a history of suicide attempts compared to depressed older adults and non-depressed older adults[14, 39, 40]. We have shown that PST is effective for treating depression[19], disability associated with depression[20] and mild cognitive impairments[21], three major risk factors for suicide risk in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Deficits in problem solving abilities are particularly pronounced in older adults with a history of suicide attempts compared to depressed older adults and non-depressed older adults[14, 39, 40]. We have shown that PST is effective for treating depression[19], disability associated with depression[20] and mild cognitive impairments[21], three major risk factors for suicide risk in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…In some individuals who die by suicide, there is no mental illness detected prior to suicide (De Gioannis & De Leo 2012;Pridmore 2011). However, the assessment and treatment of depression is largely recognized as the key tenet of elderly suicide prevention (Wiktorsson et al 2011) and research, as evidenced by numerous studies (Bergman Levy et al 2011;Conwell & Duberstein 2005;Gibbs et al 2009;Minayo & Cavalcante 2010;Miyabayashi 2002;Takahashi et al 1995;Tsoh et al 2005). Social work participants in Kim's (2013) study expressed deep concern about the 'overemphasis on depression as a primary cause of elderly suicide', describing the 'medical framing of elderly suicide' as a barrier to intervention:…”
Section: Traditional Approaches To Understanding Suicide and Suicidalmentioning
confidence: 99%
“…Lack of feeling connected to others [84] and poor social problem solving [85] can amplify the risk for suicide. Szanto and colleagues reported that older suicide attempters committed significantly more errors in social emotion recognition and showed poorer global cognitive performance than elders with no psychiatric history [86].…”
Section: Cognition and Decision Processesmentioning
confidence: 99%